2020
DOI: 10.35940/ijitee.d1599.029420
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia Classification using Deep Learning in Healthcare

Abstract: There is a great growing interest in the domain of deep learning techniques for identifying and classifying images with various datasets. An enormous availability of datasets (e.g. ChestX-Ray14 dataset) has developed a keen interest in deep learning. Pneumonia is a disease that is caused by various bacteria, virus etc. X-ray is one of the major diagnosis tools for diagnosing pneumonia. This research work mainly proposes a convolutional neural system (CNN) model prepared without any preparation to group and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The proposed work has been tested using chest X-ray & CT dataset. In the given study by (Verma & Prakash, 2020), it has been demonstrated that how one can classify the true and false cases of pneumonia easily from a small dataset of X-ray images using CNN approach along with different data augmentation techniques for improving the classification accuracies which will help in improving the validation and characterization of exactness of the CNN model. (Acharya & Satapathy, 2020) have proposed an automatic detection of pneumonia from chest radiography image using the deep Siamese based neural network.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed work has been tested using chest X-ray & CT dataset. In the given study by (Verma & Prakash, 2020), it has been demonstrated that how one can classify the true and false cases of pneumonia easily from a small dataset of X-ray images using CNN approach along with different data augmentation techniques for improving the classification accuracies which will help in improving the validation and characterization of exactness of the CNN model. (Acharya & Satapathy, 2020) have proposed an automatic detection of pneumonia from chest radiography image using the deep Siamese based neural network.…”
Section: Related Workmentioning
confidence: 99%
“…During each epoch, a random augmentation of images that preserve collinearity and distance ratios was performed. According to (Verma & Prakash, 2020), this technique helps to improve and add some effective knowledge about the data for enhancing the classification accuracy of the images and better results. Besides that, the model trained with data augmentation is more robust and can generalize better.…”
Section: Data Augmentationmentioning
confidence: 99%
“…For detection the disease, many classi cation algorithms are employed to categorize patient data. [4] During training period, the classi cation model [5] is trained using information from the standard dataset.…”
Section: Introductionmentioning
confidence: 99%
“…As for the intermediate stage, it started with the emergence of machine learning algorithms like support vector machine (SVM), k-nearest neighbor (KNN), Naïve bayes (NB), and random forest (RF) [11] [12]. The research in the current period i.e., the third stage focused on the use of deep learning models, speci cally convolutional neural network (CNN) models, such as VGGNetm ExNet, and GoogleNet [13] The rest of this paper is organized as follows: In the section 2, we present the most prominent previous studies, speci cally those that focused on deep learning models and supported their results with a performance curve. Section 3 presents the proposed model in detail.…”
Section: Introductionmentioning
confidence: 99%